Crosslinked sulfonated poly(ether ether ketone) proton exchange membranes for direct methanol fuel cell applications - Zhong, Shuangling; Cui, Xuejun; Cai, Hongli; Fu, Tiezhu; Zhao, Chengji; Na, Hui (Journal of power sources, 2007)
In the present study, a series of the crosslinked sulfonated poly(ether ether ketone) (SPEEK) proton exchange membranes were prepared. The photochemical crosslinking of the SPEEK membranes was carried out by dissolving benzophenone and triethylamine photo-initiator system in the membrane casting solution and then exposing the resulting membranes after solvent evaporation to UV light. The physical and transport properties of crosslinked membranes were investigated. The membrane performance can be controlled by adjusting the photoirradiation time. The experimental results showed that the crosslinked SPEEK membranes with photoirradiation 10 min had the optimum performance for proton exchange membranes (PEMs). Compared with the non-crosslinked SPEEK membranes, the crosslinked SPEEK membranes with photoirradiation 10 min markedly improved thermal stabilities and mechanical properties as well as hydrolytic and oxidative stabilities, greatly reduced water uptake and methanol diffusion coefficients with only slight sacrifice in proton conductivities. Therefore, the crosslinked SPEEK membranes with photoirradiation 10 min were particularly promising as proton exchange membranes for direct methanol fuel cell (DMFC) applications.